The disparity between species description and conservation assessment: A case study in taxa with high rates of species discovery. (April 2018) - Tapley, Benjamin; Michaels, Christopher J.; Gumbs, Rikki; Böhm, Monika; Luedtke, Jennifer; Pearce-Kelly, Paul; Rowley, Jodi J.L.
Abstract: The IUCN Red List of Threatened Species (Red List) details the extinction risk of the world's species and presents an important biodiversity indicator for conservation policy. Its continued utility relies on it containing up-to-date information on the extinction risk of species. This requires both regular reassessments and the timely assessment of newly described species. We provide an overview of the status of amphibian Red List assessments to highlight the difficulties of keeping assessments updated for species groups with high rates of species description. Since the publication of the IUCN's Global Amphibian Assessment in 2004, description rates of new species and assessment rates were initially similar; yet while the former has remained consistent, the latter has recently sharply declined. Currently 61.3% of amphibian species are either Not Evaluated or have out-of-date assessments. The situation is particularly problematic in countries with the richest amphibian diversity, which typically have the highest rates of amphibian species discovery and face the greatest threats. Efforts to keep the Red List up-to-date are primarily limited by funding, we estimate that an annual investment of US 170, 478–319, 290 is needed to have an up-to-date Red List for amphibians. We propose suggestions to increase assessment rates by improving the availability of data relevant to the process: authors of species descriptions or taxonomic revisions should publish information relevant to Red List assessments. Taxonomic journals should suggest inclusion of such information in their author guidelines. We suggest that contributors with significant input into assessments should be rewarded with co-authorship of published assessments. Highlights: Since 2004 there has been 25% increase in known amphibian species. Extinction risk assessments are out-of-date or lacking for 61% of amphibian species. Species descriptions should contain data relevant to species' conservation status.